Limestone-siliceous and siliceous concretes thermal damaging at high temperature. (20th December 2019) - Mastori, H.; Piluso, P.; Haquet, J.-F.; Denoyel, R.; Antoni, M.
Highlights: Three tsiliceous (S) and limestone-siliceous concretes (L). At moderate temperatures, mass loss turns similar for both S and L concretes. Mercury porosimetry demonstrates larger porosity of L concretes when T>500°C. At T = 1000 °C, L concretes exhibit a larger specific area than S concretes. Abstract: Limestone-siliceous and siliceous concretes are used in reactor pits of French nuclear power plants. In case of severe nuclear reactor accident, failure of the reactor vessel would lead to interaction between molten corium (hot melt of nuclear fuel) and concrete. This paper focuses on the thermal degradation of both limestone-siliceous and siliceous concretes till 1000 °C. Thermo-Gravimetric Analysis (TGA) and Mercury Intrusion Porosimetry (MIP) are used to measure mass loss and porosity modification. As concretes are heterogeneous materials, sampling and representativeness have been addressed. TGA experiments show larger mass loss for limestone-siliceous concretes due to the decarbonation of calcium carbonate gravels when T > 800 °C. MIP experiments demonstrate a 100% increase of porosity for limestone-siliceous (resp. siliceous) concretes when T > 500 °C (resp. T > 800 °C). The consequences of these results are discussed in the frame of experimental tests on prototypical corium systems aimed at describing the key-phenomena involved in molten corium concrete interaction.